Character Education from the Perspective of the Qur’an and Hadith as a Foundation for Shaping a Complete Muslim Personality - Mukhlis Mukhlis; Mahyuddin Barni; Abdul Basir; Ali Muammar (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
This study aims to conceptually examine how the Qur’an and Hadith serve as the fundamental foundations for shaping human character, emphasizing the importance of integrating knowledge, faith, and righteous deeds in education. This research employs a library research method, based on the review of several articles, journals, and other scientific works related to the entered keywords through Google Scholar, as well as utilizing the POP (Publish or Perish) application to find studies relevant to this topic. The findings reveal that Islamic character education does not merely focus on shaping outward behavior but rather emphasizes the purification of the soul (tazkiyatun nafs) and the strengthening of internal moral values. Therefore, character education grounded in the Qur’an and Hadith holds high relevance in developing a generation of Muslims with noble character, competitiveness, and positive contributions to society and global civilization